Oral Health-Related Awareness, Practices (Attitude) and Determination of the Level of Awareness of Periodontal Disease Risk among Diabetic Patients - O.O. Onigbinde; E.B. Dosumu; A.A. Oyapero (Nigerian Dental Association, 2020)
Background: A comprehensive knowledge about the mutual influence between diabetes and periodontitis is decisive for the successful treatment of both diseases. The present study aimed at assessing the level of awareness of the relationship between diabetes and periodontitis among the diabetic patients. Material and Methods: This survey was conducted among one hundred and fifty two diabetic patients who were recruited using a systematic  random sampling technique. Participants completed a self-administered, structured questionnaire each after obtaining institutional ethical approval. Descriptive statistics and frequency distributions were used for demographic variables and chi squared test was used when comparing categorical data. Statistical significance was determined as p<0.05. Results: The knowledge of diabetes on their increased risk for oral diseases was low. Only 49.8% of the sample population knew about the mutual relationship between diabetes and periodontitis. Their attitude towards maintaining good oral health was also not up to the desired standard.  Among the participants, only 63.2%, 11.8% and 15.8% brushed their teeth once daily, used dental floss regularly and visited the dentist once yearly respectively. Conclusion: There is an insufficient knowledge among the study group about the mutual relationship between diabetes and periodontitis. This lack of knowledge emphasized the need for more information about oral health care in patients with diabetes mellitus.